Triphasic Metal Oxide Photocatalyst for Reaction Site-Specific Production of Hydrogen Peroxide from Oxygen Reduction and Water Oxidation - Kim, Keon-Han; Kim, Se-Jun; Choi, Won Ho; Lee, Heebin; Moon, Byeong Cheul; Kim, Gi Hwan; Choi, Jae Won; Park, Dong Gyu; Choi, Jong Hui; Kim, Hyungjun; Kang, Jeung Ku (Wiley-VCH Verlag, 2022)
The search for photocatalysts allowing the highly active, selective, and stable conversion of molecular oxygen into hydrogen peroxide is of worldwide interest. Here, the authors report the efficient conversion of O-2 into H2O2 with approximate to 100% selectivity and stable cycle stability by a triphasic metal oxide photocatalyst with a cobalt hydroxide carbonate nanosheet phase for water oxidation as well as iron oxide and titanium oxide phases of a core-shell morphology for charge transfer and oxygen reduction, denoted as CFT. The different surface energies of 0.78 (anatase) and 0.93 J m(-2) (rutile) for titanium oxide and 1.39 J m(-2) for iron oxide result in a core-shell morphology. The band gaps for iron oxide (2.02 eV), titanium oxide (approximate to 3 eV), and cobalt hydroxide carbonate (3.80 eV) sites reveal that the CFT photocatalyst allows visible-to-UV light absorption. The O-18(2) isotope-labeling experiments prove that the core-shell structure promotes hole transfer toward the water oxidation site. Additionally, the hole-induced H2O2 decomposition at the oxygen reduction site is efficiently hindered. Moreover, the photogenerated electrons transfer toward the oxygen reduction site to produce H2O2 from O-2 with approximate to 10-fold higher activity than those by conventional single- or dual-phase photocatalysts, while giving robust cycle stability.